Rhythms of the day: How electronic media and daily routines influence mood during COVID‐19 pandemic. Issue 2 (16th November 2021) - Zubek, Julian; Ziembowicz, Karolina; Pokropski, Marek; Gwiaździński, Paweł; Denkiewicz, Michał; Boros, Anna
Abstract: This study aims to investigate how daily activities affect mood in the context of social distancing guidelines enforced during the COVID‐19 pandemic. Using Ecological Momentary Assessment (EMA) administered four times a day during a 2‐week period, we asked participants ( N  = 91) about their mood and the activities they engaged in. Seven individuals were selected for a follow‐up, open‐ended questionnaire. Results show that a stable routine, including physical exercise, hobbies, regular sleep hours, and minimal time spent in front of the computer, helps maintain a good mood. Coping strategies such as planning and scheduling help keep routines and circadian rhythms stable. Face‐to‐face contact is associated with a more positive mood, while similar interaction through electronic communication has a less positive effect. We observe an effect related to the infodemic phenomenon: Daily reports on COVID‐19 cases and deaths affect mood fluctuations. This is an important consideration in shaping public information policies.